2017
DOI: 10.21037/qims.2017.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Towards MRI temperature mapping in real time—the proton resonance frequency method with undersampled radial MRI and nonlinear inverse reconstruction

Abstract: IntroductionRecent developments in MRI provide a new method for real-time imaging (1) which offers so far unsurpassed diagnostic capabilities in a large variety of clinical fields. Respective applications range from cardiac MRI without ECG synchronization and during free breathing (2) to real-time studies of blood flow (3), swallowing (4), dysphagia (5), esophageal functions (6), dynamics of the temporomandibular joint (7), respiration-induced flow of the cerebrospinal fluid (8,9) as well as movements of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…However, the system has a limitation of invasive single-point measurement of temperature. Previous studies have shown that temperature monitoring during HIFU treatment is possible with non-invasive spatial temperature monitoring tools, such as ultrasound and magnetic resonance imaging (MRI) [6, 39, 40]. Ultrasound imaging can track temperature changes by analyzing various temperature-dependent properties such as speed of sound, attenuation, and echo strain of tissue [19, 41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the system has a limitation of invasive single-point measurement of temperature. Previous studies have shown that temperature monitoring during HIFU treatment is possible with non-invasive spatial temperature monitoring tools, such as ultrasound and magnetic resonance imaging (MRI) [6, 39, 40]. Ultrasound imaging can track temperature changes by analyzing various temperature-dependent properties such as speed of sound, attenuation, and echo strain of tissue [19, 41].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound imaging can track temperature changes by analyzing various temperature-dependent properties such as speed of sound, attenuation, and echo strain of tissue [19, 41]. MRI thermometry can measure the interstitial tissue temperature by utilizing temperature-sensitive MR parameters [6, 40]. Recent non-invasive temperature monitoring techniques, including 3D IR thermal imaging and ultrasound thermometries using passive mapping and shear wave elastography [4246], can also be incorporated with the proposed HIFU system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to temperature imaging, other advantages of MRI relate to the measurement of further heat‐induced changes, including thermal convection, moisture‐loss and moisture‐redistribution, starch gelatinization, protein denaturation, and phase transition either before, during, or after the heating process (Nott & Hall, 2005). Therefore, this method could be a unique tool to obtain three‐dimensional images and to gain insights into local and dynamic process phenomena of food temperature, where the response time is sufficient (Ebrahimnejad et al., 2018; B. P. Hills et al., 1999; Mariette et al., 2012; Z. Zhang et al., 2017). Furthermore, MRI remains limited in its applicability even in research work by its complexity and costs.…”
Section: Methods Using Physical Effects To Determine the Samples’ Tem...mentioning
confidence: 99%
“…Therefore, this method could be a unique tool to obtain three-dimensional images and to gain insights into local and dynamic process phenomena of food temperature, where the response time is sufficient (Ebrahimnejad et al, 2018;B. P. Hills et al, 1999;Mariette et al, 2012;Z. Zhang et al, 2017).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…A green laser with a wavelength of 520 nm was also combined into the ablation laser beam to offer visual indication of the ablation laser location using an MR-compatible fiberscope. A GRE sequence with parameters repetition time (TR)/echo time (TE) = 45/13.8 ms, flip angle = 12°, slice thickness = 8 mm, number of slices = 1, pixel size = 0.625 mm by 0.625 mm, and field of view = 160 mm by 160 mm was implemented to acquire both a magnitude and phase image at a time resolution of 10 s. This could be further accelerated by introducing advanced pulse sequences ( 51 ). The magnitude image directly gives the update of tissue morphology during the laser ablation.…”
Section: Ex Vivo Trialmentioning
confidence: 99%